Effects of extracorporeal cardiopulmonary resuscitation on neurological and cardiac outcome after ischaemic refractory cardiac arrest. Issue 5 (August 2018) - Cesana, Francesca; Avalli, Leonello; Garatti, Laura; Coppo, Anna; Righetti, Stefano; Calchera, Ivan; Scanziani, Elisabetta; Cozzolino, Paolo; Malafronte, Cristina; Mauro, Andrea; Soffici, Federica; Sulmina, Endrit; et al.
Background: Extracorporeal cardiopulmonary resuscitation is increasingly recognised as a rescue therapy for refractory cardiac arrest, nevertheless data are scanty about its effects on neurologic and cardiac outcome. The aim of this study is to compare clinical outcome in patients with cardiac arrest of ischaemic origin (i.e. critical coronary plaque during angiography) and return of spontaneous circulation during conventional cardiopulmonary resuscitation vs refractory cardiac arrest patients needing extracorporeal cardiopulmonary resuscitation. Moreover, we tried to identify predictors of survival after successful cardiopulmonary resuscitation. Methods: We enrolled 148 patients with ischaemic cardiac arrest admitted to our hospital from 2011–2015. We compared clinical characteristics, cardiac arrest features, neurological and echocardiographic data obtained after return of spontaneous circulation (within 24 h, 15 days and six months). Results: Patients in the extracorporeal cardiopulmonary resuscitation group ( n =63, 43%) were younger (59±9 vs 63±8 year-old, p =0.02) with lower incidence of atherosclerosis risk factors than those with conventional cardiopulmonary resuscitation. In the extracorporeal cardiopulmonary resuscitation group, left ventricular ejection fraction was lower than conventional cardiopulmonary resuscitation at early echocardiography (19±16% vs 37±11 p <0.01). Survivors in both groups showed similar left ventricular ejection fraction 15 days and 4–6 months after cardiac arrest (46±8% vs 49±10, 47±11% vs 45±13%, p not significant for both), despite a major extent and duration of cardiac ischaemia in extracorporeal cardiopulmonary resuscitation patients. At multivariate analysis, the total cardiac arrest time was the only independent predictor of survival. Conclusions: Extracorporeal cardiopulmonary resuscitation patients are younger and have less comorbidities than conventional cardiopulmonary resuscitation, but they have worse survival and lower early left ventricular ejection fraction. Survivors after extracorporeal cardiopulmonary resuscitation have a neurological outcome and recovery of heart function comparable to subjects with return of spontaneous circulation. Total cardiac arrest time is the only predictor of survival after cardiopulmonary resuscitation in both groups.